Perancangan Design UI/UX Pada TAM Collection Featuring KTJ Berbasis Website Menggunakan Metode Design Thinking - Jujuk Jurani; Tri Rochmadi; Asti Ratnasari; Avrillaila Akbar Harahap (Universitas Komputer Indonesia, 2026)
TAM Collection Featuring KTJ still has limitations in presenting product catalogs digitally, so it requires a more effective and easy-to-use interface design. This study aims to design a user interface and user experience (UI/UX) for the product catalog website that suits user needs. The method used is Design Thinking. The stages in this method include empathize, define, ideate, prototype, and test. Data collection was carried out through interviews and questionnaires. The design results were realized in the form of a website prototype. The System Usability Scale (SUS) was used to assess usability for 20 respondents. The test results obtained a SUS score of 74.98 which is included in grade B and is in the feasible category for implementation.